2008
DOI: 10.3382/ps.2008-00107
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Stressors on Normal Intestinal Microbiota, Intestinal Morphology, and Susceptibility to Salmonella Enteritidis Colonization in Broilers

Abstract: In modern poultry production systems, environmental stressors may influence bird performance and susceptibility to pathogens such as Salmonella Enteritidis. Experiments were conducted to determine the influence of 24-h feed withdrawal and 24-h exposure to high temperature (30 degrees C) on intestinal characteristics of broilers. Attachment of Salmonella Enteritidis to ileal tissue was determined using an in vitro ileal loop assay. Changes in commensal intestinal microbial populations were determined using dena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
224
2
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(258 citation statements)
references
References 48 publications
(54 reference statements)
12
224
2
8
Order By: Relevance
“…Hao et al (2012) showed that in the first 10 h of heat stress, no intestinal damage was observed in broilers. Intestinal injury related to heat stress was reported after 24 h by Burkholder et al (2008), however, which is in line with our study, where birds were exposed for 4 days and each day for 8 h, a total of 32 h of heat stress. Quinteiro-Filho et al (2010 did not find differences in villus height and crypt depth in the intestines from chickens subjected to heat stress for 6 days, which may indicate that the birds have the capacity to adapt to this condition.…”
Section: Resultssupporting
confidence: 51%
See 2 more Smart Citations
“…Hao et al (2012) showed that in the first 10 h of heat stress, no intestinal damage was observed in broilers. Intestinal injury related to heat stress was reported after 24 h by Burkholder et al (2008), however, which is in line with our study, where birds were exposed for 4 days and each day for 8 h, a total of 32 h of heat stress. Quinteiro-Filho et al (2010 did not find differences in villus height and crypt depth in the intestines from chickens subjected to heat stress for 6 days, which may indicate that the birds have the capacity to adapt to this condition.…”
Section: Resultssupporting
confidence: 51%
“…While the birds rested during the entire heat period (albeit with spread wings and panting), they rapidly compensated for this by rapid feed intake during the remaining light period. Such behaviour might have influenced the gut mucosal damage; Burkholder et al (2008) showed that intestinal damage occurs due to heat stress and feed withdrawal. Therefore, while the gut was not empty at necropsy, we cannot exclude a degree of mucosal damage due to feed deprivation caused by heat stress.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although knowledge of the ideal gut microbiota is still incomplete, it is apparent that a variety of diets can equally support optimal broiler performance and maintain a healthy gut microbial balance (Torok et al 2011b). Several factors can influence the host's gut microbiota, including age, genetics, rearing environment and stress, although the greatest determinant by far is the host's diet (Lu et al 2003;Burkholder et al 2008;Torok et al 2009Torok et al , 2011bLumpkins et al 2010). All these factors also have the potential to influence the animal's performance as measured by growth rate, feed efficiency or productivity, hence indicating a close relationship between gut microbiota and animal performance (Torok et al 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…(Durant et al 1999;Yamauchi et al 2006;Burkholder et al 2008). Other predisposing conditions such as mucosal damage (of gut or reproductive tract) and immunosuppression caused by stress can contribute to increased morbidity of gastrointestinal and reproductive tract and decreased performance or mortality of birds (Yamauchi et al 2006;Burkholder et al 2008).…”
Section: Introductionmentioning
confidence: 99%